From Fantasy to Franchise: Dragonlance and the Privatization of Genre. Issue 2 (July 2017) - Robertson, Benjamin J.
Abstract : This essay examines the relationship between genre and franchise though a discussion of the Dragonlance series, a collection of pre-fabricated adventures for Advanced Dungeons and Dragons adapted into a series of novels. Because of the sheer number of these novels (approximately 200), the fiction set in the AD&D campaign setting known as Krynn far surpasses the scope of the original adventures in terms of narrative, character, geographical location, and historical situation. The sprawling nature of the novels, which implicitly seek to be an exhaustive account of Krynn and everything that happens there, would make Dragonlance one of the longest series in the history of generic fantasy. However, as I demonstrate, the development of the Dragonlance narrative takes place in the context of a franchise that turns away from the conventions of genre fantasy. The double origin of Dragonlance as both a setting for adventures in the AD&D game system and as a series of fantasy novels creates both the mechanistic feel of the early novels (those that were adapted directly from the pre-fabricated adventures and even from actual gaming sessions) as well as opportunities for the novels to eventually break from the conventions of generic fantasy, especially the latter's particular concern with endings. My consideration of Dragonlance not only offers a consideration of the merely generic texts with which this special issue concerns itself, but also a means by which critics might consider franchises as objects.